Singmaster’s Conjecture In The Interior Of Pascal’s Triangle - Matomäki Kaisa; Radziwiłł Maksym; Shao Xuancheng; Tao Terence; Teräväinen Joni (OXFORD UNIV PRESS, 2025)
Singmaster's conjecture asserts that every natural number greater than one occurs at most a bounded number of times in Pascal's triangle; that is, for any natural number t >= 2, the number of solutions to the equation ((n)(m)) = t for natural numbers 1 <= m < n is bounded. In this paper we establish this result in the interior region exp(log(2/3+epsilon) n) <= m <= n - exp(log(2/3+epsilon) n) for any fixed epsilon > 0. Indeed, when t is sufficiently large depending on epsilon, we show that there are at most four solutions (or at most two in either half of Pascal's triangle) in this region. We also establish analogous results for the equation (n)(m) = t, where (n)(m) := n(n - 1) . . . (n - m + 1) denotes the falling factorial.